FRAGMENTASI KEAGAMAAN DAN DINAMIKA SOSIAL-BUDAYA ARAB PRA-ISLAM: REKONSTRUKSI SOSIOHISTORIS PERADABAN MEKKAH - Muhammad Alaika Rahim; Muhammad Rayya Akmal; Rasyid Hidayatullah (PT. Saha Kreasi Indonesia, 2025)
The phenomenon of religious fragmentation and socio-cultural dynamics in pre-Islamic Mecca reveals a society far more complex than the oversimplified “Jahiliyyah” narrative, making it essential to examine for understanding the foundations of Islam’s emergence. The sources of this study include the Qur’an, the Prophetic traditions, and scholarly literature that historically document the social, economic, and religious life of pre-Islamic Arabian society. The primary aim of this research is to reconstruct the relationship between diverse belief systems and Mecca’s socio-economic structures, and to explain how their interaction shaped the trajectory of the civilization prior to Islam. Using a qualitative method grounded in library research and descriptive-historical analysis, the data were examined through document criticism, thematic reduction, and triangulation to produce a comprehensive and accountable interpretation. The findings show that the overlap between polytheistic practices, tribal dominance, intensive trade activity, and pervasive social inequality created a deep moral and spiritual unrest within society. This condition opened the way for the emergence of Islam as a system that introduced principles of justice, equality, and moral renewal for the Meccan community.